La Gestiòn Administrativa y la calidad del servicio al cliente en el Hotel el Molino periodo 2018 - Espinoza Fernández, Odalys Jazmín (2019)
The present investigation analyzes the relation that exists between the Administrative Management and the Quality of the Service to the Client in the "Hotel the Mill", in the City of Riobamba; This has great attractions and there is a large number of local, national and international tourists, which is why in this case study will determine the importance of the application of quality standards and good management, to obtain a higher level of excellence in the service, in order that the completion of administrative activities proceed more efficiently and provide a greater degree of satisfaction to guests. The administrative management through its 4 phases, allows to optimize the scarce resources to achieve the desired objectives, in this way an efficient management of the administrative activities of a company is obtained. On the other hand, the quality of customer service in this research, is measured through the servqual model to determine the expectations and perceptions of customers during their time at the hotel. Two populations, internal and external, were used to determine the effectiveness of both variables and for this purpose, surveys and interviews were applied to gather the necessary information for the realization of this project. Finally, the data obtained through tables is analyzed. Finally we proceed to the conclusions and recommendations of the case study to determine the fulfillment of the proposed objectives.